Misconceptions: An Analysis of Certainty of Response Index (CRI) on Photosynthesis Materials for Junior High School Students - Marzuki, M; Diknasari, Meiti (Biosfer: Jurnal Tadris Biologi, 2022)
This research aimed to identify the misconceptions experienced by the eighth-grade students of junior high school in Bandar Lampung on photosynthesis material. Also, this research aimed to investigate the causes of the misconceptions. The research method was qualitative, with three schools randomly selected based on their accreditation, namely accreditation A, B, and C. The data collecting techniques used in this research were multiple choice objective tests accompanied by the reasons and column Certainty of Response Index (CRI). Furthermore, the researchers also interviewed the teachers. The analysis showed that the highest percentage of misconceptions appeared in six question indicators, with a percentage above 50%. This result showed that the percentage of students who experienced misconceptions about photosynthesis material was greater than students who understand the concept and do not know the concept.ABSTRAK: Penelitian ini bertujuan untuk mengidentifikasi miskonsepsi peserta didik kelas VIII SMP Negeri sekota Bandar Lampung pada materi fotosintesis, serta penyebab dari adanya miskonsepsi pada peserta didik tersebut. Metode pada penelitian ini adalah metode kualitatif. Pengambilan sampel menggunakan teknik random sampling dengan tiga tempat sekolah yang akan dijadikan bahan penelitian berdasarkan dari akreditasi sekolah SMP Negeri tersebut yaitu akreditasi (A, B, dan C). Teknik pengumpulan data yang digunakan dalam penelitian ini adalah tes objektif multiple choice yang disertai alasan dan kolom Certainty Of Response Index (CRI), dan wawancara kepada pendidik. Data hasil analisis menunjukkan miskonsepsi dengan persentase terbesar muncul pada 6 indikator soal dengan persentase di atas 50%. Hal ini menunjukkan bahwa persentase persentase peserta didik yang mengalami miskonsepsi pada materi fotosintesis lebih besar dibandingkan peserta didik yang paham konsep dan tidak tahu konsep.